CMC development of [14C]-labeled sotorasib for the conduct of microtracer human ADME study - Sonika Sharma; Prashant Agarwal; Andrew T. Parsons; James E. Huckle; Tiffany L. Correll (SpringerOpen, 2023)
Abstract Human absorption, distribution, metabolism, and excretion (hADME) studies of new drugs are required for global regulatory filings. Recent advances in high sensitivity analytical technologies have enabled microtracer hADME studies wherein very low radioactive doses can be administered to healthy volunteers to study drug pharmacokinetic profile. Microtracer hADME studies are advantageous to accelerate study timelines during drug development. However, there are limited examples in peer-reviewed journals that highlight the key chemistry, manufacturing, and control (CMC) development challenges and requirements for enabling these clinical microtracer hADME studies. The current manuscript summarizes the CMC activities, risk assessment, and mitigation strategies that were put in place and executed to enable and accelerate the microtracer hADME study of [14C]-labeled sotorasib (AMG 510, compound 1). Sotorasib is a first in class KRASG12C inhibitor used to treat non-small cell lung cancer (NSCLC) in patients with a KRASG12Cmutation (Canon et al., Nature 575:217-223, 2019). The key CMC activities included the synthesis of low nanocurie [14C]-labeled AMG 510 drug substance, development of a drug-in-bottle (DIB) formulation, use of simulation software to predict absorption profiles, associated drug substance and drug product analytical control strategies development, and the utilization of accelerator mass spectrometry (AMS) as a CMC tool enabling low radioactive strength formulation analysis.